Reaction, structure and properties of eco-friendly geopolymer cement derived from mechanically activated pumice. Issue 4 (15th February 2023) - Szabó, Roland; Kristály, Ferenc; Nagy, Sándor; Singla, Rashmi; Mucsi, Gábor; Kumar, Sanjay
Abstract: The suitability of pumice, an altered volcanic rock, for the synthesis of geopolymer cement has been investigated. The reactivity of pumice was improved by mechanical activation (MA) in a stirred media mill for various rotor speeds (3 and 5 m/s) and residence times (ranging from 1 to 10 min), respectively. MA resulted into increase in specific surface area (SSA). The effect of SSA of pumice on reactivity is evident from the increase in lime adsorption capacity, which increased from 70.7 mg CaO/g solid material to 234.7 mg CaO/g solid material and the area under the calorimetric peak which increased from 4 mJ to 16.6 mJ and from 9.3 to 27.2 mJ at 27 and 60 °C aging temperatures, respectively. X-ray powder diffraction (XRD) revealed that amorphization increased up to 7% as a result of MA on the particles. Amorphous content has further increased by another 2% after geopolymerization, which can be attributed to consumption of quartz which formed reaction products. A positive correlation has been found between milling time, area under calorimetric peak and compressive strength. Geopolymer with the highest strength (13.8 MPa) was made using pumice with the highest SSA (3838 cm 2 /g). These results are encouraging and point to the significant potential of the use of pumice as an alternative material to develop an eco-friendly geopolymer cement that contributes toward reducing the carbon dioxide emission associated with the cement production.